A Systematic Review Analysis of Character Education Social Care in Elementary School - Jamo, Maryam Suleiman (Journal of Basic Education Research, 2023)
Purpose of the study: The main objective of this research is to determine how social care character education is implemented at the elementary school level. Researchers are interested in doing this research because they see that there are still few who do similar research Methodology: The method used is System Literature Review. The population in the study were all articles related to social care character education at the elementary school level. The sample used was 16 articles related to the topic being studied. Main Findings: This research showed that social care character education in elementary schools is carried out well with various efforts. Social care character education can be done in various ways. The ways that schools can do this can be verbal or non-verbal, including integration in self-development programs, integration in subjects, and integration in school culture. Integrating the value of caring in self-development programs through school activities includes routine, spontaneous, exemplary, and conditioning. Novelty/Originality of this study: Through this research, social care character education in elementary schools is carried out well with various efforts. Social care character education can be done in various ways